Mechanisms controlling the acquisition of a cardiac phenotype by liver stem cells - Muller-Borer, Barbara J.; Cascio, Wayne E.; Esch, Gwyn L.; Kim, Hyung-Suk; Coleman, William B.; Grisham, Joe W.; Anderson, Page A. W.; Malouf, Nadia N. (East Carolina University, 2007)
The mechanisms underlying stem cell acquisition of a cardiac phenotype are unresolved. We studied early events during the acquisition of a cardiac phenotype by a cloned adult liver stem cell line (WB F344) in a cardiac microenvironment. WB F344 cells express a priori the transcription factors GATA4 and SRF, connexin 43 in the cell membrane, and myoinositol 1,4,5-triphosphate receptor in the perinuclear region. Functional cell– cell communication developed between WB F344 cells and adjacent cocultured cardiomyocytes in 24 h. De novo cytoplasmic [Ca2 +]c and nuclear [Ca2+ ]nu oscillations appeared in WB F344 cells, synchronous with [Ca2+ ]i transients in adjacent cardiomyocytes. The [Ca2 +] oscillations in the WB F344 cells, but not those in the cardiomyocytes, were eliminated by a gap junction uncoupler and reappeared with its removal. By 24 h, WB F344 cells began expressing the cardiac transcription factors Nkx2.5, Tbx5, and cofactor myocardin; cardiac proteins 24 h later; and a sarcomeric pattern 4–6 days later. Myoinositol 1,4,5-triphosphate receptor inhibition suppressed WB F344 cell [Ca2 +]nu oscillations but not [Ca2+ ]c oscillations, and L-type calcium channel inhibition eliminated [Ca2 +] oscillations in cardiomyocytes and WB F344 cells. The use of these inhibitors was associated with a decrease in Nkx2.5, Tbx5, and myocardin expression in the WB F344 cells. Our findings suggest that signals from cardiomyocytes diffuse through shared channels, inducing [Ca2 +] oscillations in the WB F344 cells. We hypothesize that the WB F344 cell [Ca2 +]nu oscillations activate the expression of a cardiac specifying gene program, ushering in a cardiac phenotype. Originally published Proc Natl Acad Sci, Vol. 104, No. 10, March 2007
Keywords: Calcium signal transduction; Cardiomyogenesis; Gap junction